LA RESCISIÓN DEL CONTRATO COLECTIVO Y SUS EFECTOS JURÍDICOS EN LAS RELACIONES INDIVIDUALES DE TRABAJO. REFORMAS NECESARIAS - SUAREZ BELTRAN, LEONCIO CRISPOLO (2016)
When we refer to the termination we are dealing with a legal act that allows rescind a contract involving labor, and therefore this leads to a series of consequences that lead not only to the limitation of certain rights products recruitment but, the total disappearance of the benefits it will bring. I mean limiting, especially when we are dealing with collective bargaining with a trade union is the worker who enters into a contract of employment, after the time established by law the right to organize is guaranteed and therefore the benefits of collective bargaining may arise; to terminate the collective contract, the worker would limit their rights under it, and lose the benefit of collective bargaining. It is noteworthy that the collective agreement stems from an agreement between the employer and the union side, but this agreement creates an obligation, as noted by our civil law, a form of extinction is the termination obligations; so through this legal open door is left for the worker can try the termination of the collective agreement if their Juico considers this not in line with their interests, under this premise and echoing the concepts listed we previously said that the termination is a mode that allows waive an obligation, but an obligation stems from an agreement or contract pursuant to Art. 1454 of the Civil Code, and points out that the contract is an act by which a party agrees to another to give, do or not do something. Each party may be one or many people. Namely that contracts may not necessarily require the contracting parties and the statement will remain obligated for these, but for this expression 6 takes the required legal effects is necessary for people to be able, to consent to the act or statement and that does not suffer from vice, falling upon lawful purpose and cause necessarily having tender, when we met these requirements to express the will, we are facing a conscious act, and therefore legally valid. Collective bargaining is also derived from free and voluntary expression of the parties and this is an act created by the workers' association or union with the consent of the union and the employer or employer therefore has its own life, so the termination of one of the subjects should only operate for one worker who expresses his will to terminate the obligation, and when a party fails to comply with the agreement, but also the seat should be noted that the termination of the collective agreement does not interfere individual relations, but in the implementation of the collective agreement, and this interference can be out of conviction or certain facts which can reach disrupt the effective implementation of collective bargaining and these may be reflected in the impact made by in urging employers to give workers join unions to prevent compliance with the agreement on collective bargaining. Also termination of collective bargaining, breaking the principles of solidarity that should exist in all trade-union.